Os componentes epifítico vascular e herbáceo terrícola da Floresta Ombrófila densa ao longo de um gradiente altitudinal na Serra da Prata, Paraná - Blum, Christopher Thomas (2013)
This study aimed to characterize the floristics, structure and spatial distribution of vascular epiphytes and ground herbs along an altitudinal gradient of the Atlantic Rainforest in the Serra da Prata mountain range (48 ‹41'59.39"W, 25 ‹36'46.39"S), Parana State, and to explore the existence of relationships among these elements and the environmental variation along the gradient. The study area has 6.3 hectares between 400 and 1,100 m a.s.l. The epiphytic component was quantified using 120 phorophytes with diameters around 35 cm with canopy crowns distributed equally at 400, 600, 800 and 1,000 m of altitude. The phorophytes were divided into six vertical zones. Dominance and coverage estimates of the epiphytes were taken for each zone. The data collection on the herbaceous synusia was done using 716 quadrats of 1x1 m placed continually in rows 2 m wide with variable length in the altitudes 500 m (208 m2), 700 m (108 m2), 800 m (200 m2) e 1,100 m (200 m2). The maximum height and the percentage of coverage of all rooted herbaceous species in the quadrats were registered. To evaluate the climatic aspects two temperature and air moisture recorders were installed at 400 and 1,000 m a.s.l. Daily data was obtained from July, 2009, until June, 2010. In total, 277 species and 30 families of vascular epiphytes were recorded. Orchidaceae included 103 species, followed by Bromeliaceae (37) and Polypodiaceae (28). The Shannon index was 4.96 nats.ind-1. Only 19.5% of the epiphytes occurred in all altitudes. Bromeliaceae had the greater structural importance along the slope. The most frequent species were Philodendron loefgrenii and Serpocaulon catharinae. Vriesea altodaserrae presented the greater structural importance in altitudes above 800 m. The most important species at 400 and 600 m a.s.l. were Aechmea organensis, Vriesea vagans and Vriesea philippocoburgii. It were recorded 158 species and 49 families of ground herbs. Dryopteridaceae included 11 species, followed by Araceae (10) and Orchidaceae (10). The Shannon index was 3.74 nats.ind-1. Only eight species (5.1%) were registered in all altitudes. Dryopteridaceae and Araceae presented highest importance along the slope. Lastreopsis amplissima, Anthurium acutum and Pleurostachys distichophylla had greater structural importance at 800 and 1,100 m a.s.l.. Below 600 m Philodendron propinquum, Stigmatopteris heterocarpa, Lomagramma guianensis and Dichorisandra thyrsiflora were the most important. For both synusiae it was observed the existence of two distinct floristic associations (submontane and montane), transitioning between 600 and 800 m, coincidently with the altitudinal limit between two types of climate, differentiated by the mean temperature of the warmest month (. 22o C . Cfa; . 22o C . Cfb). The structural composition of the epiphytic community was very similar at 400 and 600 m a.s.l., with richness and dominance values statistically greater (Duncan Multiple Range Test, p > 0,05) than the other altitudes. The steep topography of the higher altitudes generated a greater heterogeneity in the epiphytic structure due to its influence on the size and architecture of the phorophytes, resulting in structural differences between the 800 and 1,000 m. The structure of the herbaceous community also presented relationship with the topography. The altitudes 700, 800 and 1,100 m, all showing declivities higher than 60%, presented coverage and richness values statistically equal (Duncan Multiple Range Test, p > 0,05) among them, and different from the values observed at the 500 m, were the mean declivity is 32%. Therefore, the temperature seems to affect directly the floristic and sociologic composition of the studied synusiae, while the topographic characteristics show greater relationships with the structural variation along the slope.